BARRIERS TO HEALTH CARE ACCESS PERCEIVED BY ADOLESCENT GIRLS: A CROSS-SECTIONAL STUDY. - Pallavi; Jha, Milind (Student’s Journal of Health Research Africa, 2024)
Background Adolescent girls face numerous barriers when accessing healthcare, particularly in low-resource settings. These constraints include financial, cultural, and structural challenges, which significantly impact their ability to obtain timely and appropriate medical services. Addressing these barriers is essential for improving the health outcomes of adolescent girls, especially in rural areas. This study investigated the perceived constraints faced by adolescent girls in accessing healthcare in Darbhanga, Bihar, and identified socio-demographic factors associated with these barriers. Methods A cross-sectional study involved 250 adolescent girls aged 13-19 years. Data were collected using a structured questionnaire, which assessed socio-demographic characteristics and perceived healthcare barriers. Statistical analysis was performed using SPSS version 21.0. Descriptive statistics, chi-square tests, and multivariate logistic regression were used to identify significant associations between variables. Results The mean age of the participants was 16.2 years (± 1.8), with the majority (58%) being between 15 and 17 years of age. The study found that 72% of the participants reported barriers to accessing healthcare. Financial constraints (56%) were the most commonly reported, followed by structural (48%), cultural (40%), and knowledge-related barriers (32%). Family income and parental education were significantly associated with perceived barriers (p < 0.05). Multivariate analysis revealed that low family income (OR = 3.2, p < 0.001) and low parental education (OR = 2.5, p = 0.002) were the strongest predictors of healthcare access constraints. Conclusion Adolescent girls in Darbhanga face significant barriers in accessing healthcare, primarily due to financial and structural factors. Socioeconomic conditions, such as family income and parental education, play a crucial role in determining the extent of these barriers. Recommendations Policymakers should focus on reducing financial barriers and improving healthcare infrastructure, especially in rural areas. Additionally, educational programs aimed at families and communities could help address cultural and knowledge-related barriers to healthcare access for adolescent girls.